Overloaded and isolated? Preliminary findings on overcoming information challenges for incarcerated university students - Virgo, Isabel (Information Research an international electronic journal, 2025)
Introduction. This paper outlines two tentative themes identified in the initial findings of a project focusing on the information behaviour of a particular group of incarcerated university students. These students are released on licence to attend lectures and study on campus, but are still affected by prison restrictions. Theoretical background. Theories of information landscapes, small worlds and information behaviour in transition have informed this work. Methods. This paper presents analysis of the first round of data collection, using a combination of progress logs and interviews. Findings. The two key themes outlined here relate to issues of inclusion and exclusion in academic spaces. The first theme reveals issues around information overload, particularly during the induction period, while the second relates to how relationships and restrictions on and off campus affect informal information sharing. Conclusions The identification of these issues can inform support arrangements for these students, with a focus on academic library support. While these issues are unique to a particular group, they have broader implications for other categories of non-traditional higher education (HE) students.